The Effect of Toxic Relationships in Friendship on The Psychological Well-Being of Islamic University Students - Siti Rahimah; Muhammad Zainal Abidin; Mahdia Fadhila (‎‎‎TAZKIYA Journal of Psychology, 2022)
Good psychological well-being is characterized by individuals who have positive emotions and can go through difficult times that cause negative emotions to emerge. Data obtained from Riskesdas (Riset Kesehatan Dasar), in 2007 about 11.6% of the Indonesian population aged over 15 years showed emotional mental disorders characterized by symptoms of depression and anxiety. Then in 2018 the prevalence of emotional mental disorders again increased to around 9.8% (Idaiani & Isfandari, 2020). One of the factors that influence it is social support that comes from friends. Support from friends is not always positive, but also negative. Negative friends are referred to as toxic friends, namely friendships that are detrimental. The aims of this study are, (1) to describe the level of psychological well-being of Islamic University Students, (2) to describe the level of toxic relationships that occur in the circle of friends of Islamic University Students, and (3) to analyze the effect of toxic relationships on psychological well-being. to students of Islamic University Students. The method used for this research is simple regression. With a population of 11,000 people and a sample of 265 students aged 18-22 years. The results of this study are, (1) the level of psychological well-being in Islamic University Students is dominated by the very high category as many as 155 students with a percentage of 58.5%, (2) the level of toxic relationship among Islamic University Students is dominated by the low category as much as 140 students with a percentage of 52.8%, (3) there is an influence between variables toxic relationships and psychological well-being with effect level of 11.4%. Although it does not have a big influence, it is important for us to control a healthy friendship environment to maintain psychological well-being in ourselves.